Public digital art and publics: The case of Hotel Yeoville (2010) - Langa, Londiwe (My University, 2014)
This research looks at the Hotel Yeoville (2010) public digital art project and offers an analysis towards understanding how through this creative intervention a public discourse can be inclusive of marginalised African immigrant groups living in South Africa. The marginal status of African immigrant groups in South Africa, is consistently similar in the digital arts field where there is no evident critique of the public art methods employed by art practitioners in engaging these marginalised groups. The agenda of Hotel Yeoville was particularly an attempt to counter the marginalising brutal and muted representations of these groups in mainstream media. In order for this creative intervention to effect such change, its public element needed to display a public vibrancy that was inclusive of the pluralistic opinions and voices of the African immigrant groups. However this public art project revealed paradoxes and complexities that are at the core of public art practise, and also highlighted the ambivalence of a strong creative product with an uncertain public‐ness.
Keywords: Digital art.; Digital media.